Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Variabel Intervening: Studi Kasus Pada Mahasiswa/Mahasiswi Pengguna Smartphone Merek IPHONE STIE Bina Karya Tebing Tinggi Kelas Tutorial - Mayastika, Eka; Rohalya, Intan (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2023)
This research aims to determine the influence of Product Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Case Study of Students Using iPhone Brand Smartphones at STIE Bina Karya Tebing Tinggi Tutorial Class). This type of research is quantitative descriptive. The sample in this research were IPHONE brand smartphone users, tutorial class students, totaling 32 respondents. The research results show that Product Quality (X) influences the Customer Satisfaction variable (Z). The second hypothesis in this research is rejected, meaning that the Product Quality variable (X) has no effect on the Customer Loyalty variable (Y), the third hypothesis is accepted, meaning that the Customer Satisfaction variable (Z) has an effect on the Customer Loyalty variable (Y). Meanwhile, the indirect influence through the customer satisfaction variable (Z) is smaller than the direct influence on the Customer Loyalty variable. These results indicate that the customer satisfaction variable cannot be a bridging variable or a mediating variable between the Product Quality variable and customer loyalty.